2022
DOI: 10.1038/s41598-022-06608-7
|View full text |Cite
|
Sign up to set email alerts
|

On a high photocatalytic activity of high-noble alloys Au–Ag/TiO2 catalysts during oxygen evolution reaction of water oxidation

Abstract: The analysis via density functional theory was employed to understand high photocatalytic activity found on the Au–Ag high-noble alloys catalysts supported on rutile TiO2 during the oxygen evolution of water oxidation reaction (OER). It was indicated that the most thermodynamically stable location of the Au–Ag bimetal-support interface is the bridging row oxygen vacancy site. On the active region of the Au–Ag catalyst, the Au site is the most active for OER catalyzing the reaction with an overpotential of 0.60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…26) but in apparent contradiction with recent reports by Haider et al and Malik et al where Au–Ag alloy NPs on TiO 2 have shown higher photocatalytic activities compared to monometallic NPs. 55,56…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26) but in apparent contradiction with recent reports by Haider et al and Malik et al where Au–Ag alloy NPs on TiO 2 have shown higher photocatalytic activities compared to monometallic NPs. 55,56…”
Section: Resultsmentioning
confidence: 99%
“…who found photocatalytic activities to increase in the order of TiO 2 < Ag/TiO 2 < alloy Au-Ag/TiO 2 < Au/TiO 226 but in apparent contradiction with recent reports byHaider et al and Malik et al where Au-Ag alloy NPs on TiO 2 have shown higher photocatalytic activities compared to monometallic NPs 55,56. In both works, however, the experimental conditions where different and focussed on water oxidation reaction, which challenges comparison of the results.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Potapenko et al reported the atomic resolution of TiO 2 nanocrystals adsorbed under conditions of photoreaction [23]. It has also been reported that the presence of metal clusters can improve the adsorption capacity of TiO 2 [24][25][26]. We studied the effect of metal ion doping on the electrical properties of TiO 2 (001) crystal planes by comparing the adsorption behavior of gas molecules on undoped TiO 2 and Co 2+ ion-doped TiO 2 (001) crystal planes.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Specifically, the amount of energy required to drive each step beyond the equilibrium potential, known as overpotential, [19][20][21][22] provides a good metric of surface reactivity. The photo-oxidation of water on defect-free rutile (110) surfaces has been broadly explored, 19,21,[23][24][25][26][27][28][29][30][31] as well as, direct prediction of OER on rutile (110) with subsurface oxygen vacancies, [32][33][34][35][36][37][38][39][40][41][42] multiple surface coverages, 19,29,43,44 and metal nanoclusters [45][46][47][48][49][50] adsorbed on the surface provides a detailed picture of its reactivity.…”
Section: Introductionmentioning
confidence: 99%